First-Principles Study on Electronic Properties of Low-Index ZnO Surfaces - Zhao, J.H.; Han, E.J.; Liu, T.M.; Zeng, W. (Asian Journal of Chemistry, 2012)
The density functional theory plane-wave pseudopotential method was employed to study four low-index ZnO surfaces, which were (001), (100), (101) and (110) respectively. The structural parameters, band structures, density of states and the charge densities have been investigated. Present results show that the surfaces form the sequence (110) < (100) < (101) < (001) in order of increasing energy. The prediction that (110) is rather more stable. Both atoms displacements and the change of bond lengths after relaxing are observed. The changing values of (110) are the least, which is consistent with the prediction. The calculations of band structures and density of states suggest that valence bands of the four surfaces mainly consist of Zn 3d and O 2p orbitals and the conduction bands are mainly composed by O 2p states. Additionally, (110) has the narrowest band gap and the least charge density.